2015
DOI: 10.1063/1.4919759
|View full text |Cite
|
Sign up to set email alerts
|

Coherent-state storage and retrieval between superconducting cavities using parametric frequency conversion

Abstract: In superconducting quantum information, machined aluminum superconducting cavities have proven to be a well-controlled, low-dissipation electromagnetic environment for quantum circuits such as qubits. They can possess large internal quality factors, Q int > 10 8 , and present the possibility of storing quantum information for times far exceeding those of microfabricated circuits. However, in order to be useful as a storage element, these cavities require a fast "read/write" mechanism-in other words, they requi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 14 publications
1
62
0
Order By: Relevance
“…Moreover, the quest for useful quantum computations before full quantum error correction becomes available may be assisted by efficient, short-depth gate sequences based on two-or multi-qubit gates [14,15] with versatile types of interactions. In particular, parametric schemes based on tunable couplers have been proposed and recently realized as a means to achieve fast gates with high fidelities [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
mentioning
confidence: 99%
“…Moreover, the quest for useful quantum computations before full quantum error correction becomes available may be assisted by efficient, short-depth gate sequences based on two-or multi-qubit gates [14,15] with versatile types of interactions. In particular, parametric schemes based on tunable couplers have been proposed and recently realized as a means to achieve fast gates with high fidelities [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
mentioning
confidence: 99%
“…Several methods to tackle this trade-off have been demonstrated recently. These include the adjustment of the external quality factor of the storage resonator using a tunable coupler [10,11] or a flux-driven Josephson junction [12], and conversion from stationary to propagating photons using a driven transmon qubit [13] or a Josephson ring modulator [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our stabilization method presents a complementary application for the tunable response rate of a resonator. Whereas recent experiments that have realized effectively tunable quality factors are motivated by fast injection of arbitrary photon states to the resonator [11][12][13], we envisage protocols where ancillary coherent states are repeatedly stabilized and reused for various tasks. On the other hand, in previous work [21] we have shown that maintaining a coherent state in this manner may be beneficial in reducing harmful heat loads subject to quantum circuits.…”
Section: Introductionmentioning
confidence: 99%
“…which does not conserve photon number [27][28][29], and couple each device via a similar coupling to a second, lossy degree of freedom, such as a rapidly decaying qubit or readout resonator, with a full example circuit shown in FIG. 1.…”
Section: Basic Circuit Modelmentioning
confidence: 99%
“…We couple the two devices via a high-frequency, driven coupling arXiv:1510.06117v1 [quant-ph] The two transmon qubits (blue boxes) are the good quantum degrees of freedom we wish to protect, and the two readout resonators (red boxes) are lossy objects we will use for error correction. The three driven SQUID couplings have precisely tuned flux biases (black circles) to enable parametric interactions, as discussed in the supplemental material.which does not conserve photon number [27][28][29], and couple each device via a similar coupling to a second, lossy degree of freedom, such as a rapidly decaying qubit or readout resonator, with a full example circuit shown in FIG. 1.…”
mentioning
confidence: 99%